FILM SCRIPTS AS OBJECTS OF LINGUISTIC RESEARCH AND THEIR TRANSLATION CHALLENGES (SCIENCE TIME JOURNAL, 2026)
Film scripts (screenplays) are hybrid texts: written documents designed for oral performance and multimodal realization. This article offers an expanded, publication-ready review of film scripts as objects of linguistic research and of the main translation problems that emerge when scripts are adapted across languages and media. First, the article clarifies the screenplay’s status within telecinematic discourse as a form of prefabricated orality—planned discourse engineered to simulate spontaneous conversation. Second, it synthesizes key analytic approaches, including pragmatics, discourse analysis, corpus linguistics, computational stylistics, and multimodal perspectives. Third, it examines translation challenges in both pre-production adaptation and post-production audiovisual translation (AVT), focusing on the interaction of technical constraints (e.g., lip-synchrony, isochrony, subtitle space–time limits) with pragmatic meaning, cultural reference, and characterization. The article concludes with methodological recommendations and a research agenda that integrates multimodal corpora, script–screen alignment, and translation-process evidence.